(untitled) (CIPEEX, 2025)
This research aims to address the concept of ineligibility in light of Complementary Law No. 135/2010, known as the Clean Record Law, and its role in moralizing the Brazilian electoral process. Through a qualitative approach, with a review of the literature and documentation, the study investigates the constitutional foundations of ineligibility, in particular Article 14, §9, of the Federal Constitution of 1988, and addresses the legitimacy of restricting the passive political rights of individuals convicted by collegiate bodies, even without a final judgment. The results indicate that the Clean Record Law has been effective in preventing candidates with a history of impropriety or crimes against public administration from running for office, acting as an ethical filter in the electoral process. However, doctrinal criticisms indicate tensions with the principles of presumption of innocence and due process, which requires careful application by the judiciary. It is concluded that, although it represents a significant advance in the promotion of public morality, the effectiveness of the Clean Record Law depends on the combination of legal certainty, social control, and the strengthening of democratic institutions.